THE ZERO PRICE PARADOX: WHEN AND WHY ZERO PRICES ARE LESS EFFECTIVE THAN LOW PRICES IN DRIVING CONSUMER DEMAND - Zaenal Aripin; Fitriana; Faisal Matriadi (PT. Kreatif Indonesia Satu, 2024)
The zero price paradox has become an interesting phenomenon in the study of economics and consumer behavior. Although zero prices are supposed to trigger high demand, the reality is that zero prices are often less effective in encouraging consumers to take action than low prices. This shows the complexity in perceived value, consumer psychology, and economic factors that influence consumer behavior. This research aims to understand the zero price paradox phenomenon by analyzing the factors that influence the lack of effectiveness of zero prices in driving consumer demand. The research method used is qualitative, by reviewing relevant literature in the study of economics and consumer behavior. Data sources used include journals, articles and books that discuss the zero price paradox and related factors. The research results show that perceived value, consumer psychology, and economic factors such as product or service quality play an important role in explaining the zero price paradox. Consumers tend to place a higher value on the goods or services they pay for, even if the price is low. In a zero-price context, when consumers pay nothing at all, they tend to be less attached to or pay less attention to the product, which reduces motivation to use it. Additionally, low prices are often considered a better indicator of value by consumers.